2002
DOI: 10.1001/archpedi.156.5.504
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Use and Costs for Children With Attention-Deficit/Hyperactivity Disorder

Abstract: Overall costs of care for children with ADHD are comparable to costs for children with asthma and significantly greater than for the general pediatric population. Specific types of health care use and the sources of expenditures differ between children with ADHD and children with asthma. Because much ADHD-related care occurs within school and mental health settings, these figures likely underestimate the true costs of caring for children with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 26 publications
6
104
0
Order By: Relevance
“…4 Results of multiple cost studies consistently indicated that children with ADHD had higher annual medical costs than children without ADHD. [5][6][7][8][9][10][11] Treatment options for ADHD include medication management, behavioral treatment, or combination of the two, with medication management being the most cost-effective. 12 Stimulants are an effective first-line treatment option for the majority of ADHD patients, with about 70% of patients responding to treatment in the short term (within 6-10 weeks).…”
Section: Sample Selectionmentioning
confidence: 99%
“…4 Results of multiple cost studies consistently indicated that children with ADHD had higher annual medical costs than children without ADHD. [5][6][7][8][9][10][11] Treatment options for ADHD include medication management, behavioral treatment, or combination of the two, with medication management being the most cost-effective. 12 Stimulants are an effective first-line treatment option for the majority of ADHD patients, with about 70% of patients responding to treatment in the short term (within 6-10 weeks).…”
Section: Sample Selectionmentioning
confidence: 99%
“…9,11 All children ,18 years old were followed for 2 years. Between 12 810 and 14 828 households were sampled annually from the US civilian, noninstitutionalized population drawn from the previous year' s National Health Interview Survey (NHIS).…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…Total health care expenditures included direct payments to health care providers for outpatient visits, home health care, prescriptions, dental visits, hospital stays, ED visits, and other medical equipment and expenses. 11,14 We separately considered out-of-pocket (copayments and payments not reimbursed by insurance), 17 office-based, inpatient, ED, and prescription costs. To avoid bias from extreme outliers and violations of the assumptions of normality of our statistical models, 9 we calculated all expenditure results with the top 2.5% of values trimmed to the 97.5 percentile.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…An ADHD patient can cost the State approximately US$ 4,181/year due to special academic needs, 7 US$ 7,424 to 36,076/year due to criminal activities, 9 and about US$ 1,151/year due to health care utilization. 12 Recently, the incremental cost of ADHD in all age groups was estimated to range from US$ 143 to 266 billion/year in the United States alone. The educational and health care fractions of this cost for children ranged from US$ 15 to 25 billion/year and from US$ 21 to 44 billion/year, respectively.…”
Section: Introductionmentioning
confidence: 99%